The journey of murabbis in architecture pedagogy: the case of studio teaching as laboratory of passion and duty to future khalifas of the built environment - Mohd Nawawi, Norwina; Abdul Rahim, Zaiton; Denan, Zuraini; Abdul Majid, Noor Hanita; Abdul Rahim, Asiah; Abdullah, Fadzidah; Sapian, Abdul Razak; Hamat, Sufian (IDOSI Publication, 2014)
Murrabi in the context of architecture pedagogy is a “teacher” with conscience and responsibility towards the Creator Almighty Allah, Mankind and Environment. The task is to produce graduates as architects and architecture related khalifahs or stewards to enhance the built environment in God envisioned or tawhidic way. Design as the core course for architecture and studio as the laboratory or the madrasah for future architects in the making, making mistakes is part of the healthy learning process. Matrix of questions arises on how to educate the quantity of students from various background and mix, to qualify as the khalifah as he/she sets out upon graduation. How do we, teachers, the architecture murabbis, ensure and sustain the methodology of teaching to keep abreast with the expectations of the future khalifah’s amidst ever changing and demanding environment, technology and culture. This paper intends to share aspects of studio teaching methodology, the pioneering teachers of IIUM, as self-acclaimed murabbis, applied in the studio teaching and learning process within the span of 16 years. Qualitative and quantitative methodologies were applied for this study. Through literature review, observations, interviews, hands-on experience and constant feedbacks from industry, as an on-going research for constant improvement, this continuous research for “appropriate” studio teaching of the time and place would be displayed for discussion. Research findings confirm, as humans, we are fallible beings. However, the effort made with passion and sincerity throughout the 16 years had borne fruits that ignite the industry thus provides the “nor” as an incentive that motivates the architecture murabbis the zest and continuity in innovative studio teaching and learning.